Cross-Sectional Study of Work Motivation, Job Satisfaction, and Nurse Performance at Tanduale Regional General Hospital Bombana Regency - Sari, Astika Yulia; Tasnim, Tasnim; Umi Nurlila, Ratna (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Nurse performance is one of the key determinants of hospital service quality. In Regional General Hospital Tanduale, Bombana Regency, the issue of delayed salaries and high workloads may influence work motivation, job satisfaction, and ultimately performance. This study aims to Cross-Sectional Study of Work Motivation, Job Satisfaction, and Nurse Performance at Tanduale Regional General Hospital, Bombana Regency. Method: This study applied a quantitative approach with a cross-sectional design, conducted from June to July 2025. The population was 122 nurses, with a minimum sample size of 94 respondents determined using the Slovin formula. Total sampling was applied based on inclusion criteria. Data were collected through structured questionnaires and analyzed using Path Analysis with Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. Result: The results showed that extrinsic motivation had a significant effect on job satisfaction (β = 0.469; p = 0.041) and nurse performance (β = 0.735; p = 0.004). Meanwhile, intrinsic motivation did not significantly affect either job satisfaction (β = 0.325; p = 0.149) or nurse performance (β = -0.010; p = 0.962). Job satisfaction also did not significantly influence nurse performance (β = 0.211; p = 0.401) and did not act as a mediating variable. Conclusion: The study concludes that extrinsic motivation such as salary, incentives, recognition, and supportive work conditions is the dominant factor influencing both job satisfaction and nurse performance.